(untitled) (Journal of Engineering, 2016)
This research is carried out to investigate the behavior of self-compacting concrete (SCC) two-way slabs with central square opening under uniformly distributed loads. The experimental part of this research is based on casting and testing six SCC simply supported square slabs having the same dimentions and reinforcement. One of these slabs was cast without opening as a control slab. While, the other five slabs having opening ratios (OR) of 2.78%, 6.25%, 11.11%, 17.36% and 25.00%. From the experimental results it is found that the maximum percentage decrease in cracking and ultimate uniform loads were 31.82% and 12.17% compared to control slab for opening ratios (OR) of 11.11% and 6.25% respectively. Also the results showed that as OR is increased from 0.00% to 11.11%, a signifacant increase in deflection was occured. While the increase of OR from 11.11% to 25.00%, a slighlty decrease in deflection was occured compared to control slab within the entire range of loading starting from first cracking load up to ultimate load. The theoretical part of this research is adopted for both simply supported and clamped ends square slabs according to yield line theory. For simply supported slabs, the results showed a decrease in ultimate uniform loads for OR ranging between 0.00% and 25.00%. While beyond this value, an increase in the ultimate uniform load is occured. In addition, it is found that as OR was increased; the total ultimate load is decreased. Also from the theoretical analysis for clamped end slabs it is found that as OR was increased, both the ultimate uniform load and the total ultimate load were increased.